Deaths in Immigration and Customs Enforcement (ICE) detention: A Fiscal Year (FY) 2021-2023 update - Cara Buchanan; Sameer Ahmed; Joseph Nwadiuko; Annette M. Dekker; Amy Zeidan; Eva Bitrán; Thomas Urich; Briah Fischer; Elizabeth R.E. Burner; Parveen Parmar; Sophie Terp (AIMS Press, 2024)
Background: This study describes the deaths of individuals in Immigration and Customs Enforcement (ICE) detention between FY2021-2023, updating a report from FY2018-2020, which identified an increased death rate amidst the COVID-19 pandemic. Methods: Data was extracted from death reports published online by ICE. Causes of deaths were recorded, and death rates per 100,000 admissions were calculated using population statistics reported by ICE. Reports of individuals released from ICE custody just prior to death were also identified and described. Results: There were 12 deaths reported from FY2021-2023, compared to 38 deaths from FY2018-2020. The death rate per 100,000 admissions in ICE detention was 3.251 in FY2021, 0.939 in FY2022, and 1.457 in FY2023, compared with a pandemic-era high of 10.833 in FY2020. Suicide caused 1 of 12 (8.3%) deaths in FY2021-2023 compared with 9 of 38 (23.7%) deaths in FY2018-2020. COVID-19 was contributory in 3 of 11 (25%) medical deaths in FY2021-2023, compared with 8 of 11 (72.7%) in the COVID-era months of FY2020 (p = 0.030). Overall, 4 of 11 (36.3%) medical deaths in FY2021-2023 resulted from cardiac arrest in detention facilities, compared with 6 of 29 (20.3%) in FY2018-2020. Three deaths of hospitalized individuals released from ICE custody with grave prognoses were identified. Conclusions: The death rate among individuals in ICE custody decreased in FY2021-2023, which may be explained in part by the release of vulnerable individuals following recent federal legal determinations (e.g., Fraihat v. ICE). Identification of medically complex individuals released from ICE custody just prior to death and not reported by ICE indicates that reported deaths underestimate total deaths associated with ICE detention. Attentive monitoring of mortality outcomes following release from ICE custody is warranted.